Can sensitivity to temperature during germination help predict global warming vulnerability?. Issue 1 (22nd December 2015) - Cochrane, Anne
Abstract: Seed germination is vital for persistence in species that rely on seeds for post-disturbance regeneration. It is a high-risk phase and vulnerable to environmental parameters. Here, I assessed temperature sensitivity for germination in Banksia L.f. (Proteaceae) from south-western Australia, screening all 38 endemic obligate seeder species. A bi-directional temperature gradient plate with 49 temperature combinations (constant and fluctuating) between 5 and 40°C was used to profile germination temperature requirements and identify upper and lower temperature thresholds for germination. Using these data the impact of increasing temperatures on germination in these species was modelled under high and low greenhouse gas scenarios for 2050 and 2070. The results suggest that many Banksia species from the region have wide physiological tolerance for high germination temperatures, although a number of common, but geographically restricted species, such as B. praemorsa, B. oreophila and B. quercifolia, have more narrow temperature windows for germination than at least one of the rarer species ( B. verticillata ). Only B. dryandroides is expected to decline in germination in the future; however, the optimal germination timing for many species is predicted to occur later under climate warming. In conjunction with declining rainfall, this germination delay will place seedlings closer to the summer dry in this seasonal Mediterranean-climate ecosystem and thus they will be more vulnerable to desiccation. The framework developed here can be used to identify vulnerable species for monitoring of early population decline.